2016
DOI: 10.1111/jse.12190
|View full text |Cite
|
Sign up to set email alerts
|

The Gnetales: Recent insights on their morphology, reproductive biology, chromosome numbers, biogeography, and divergence times

Abstract: Ephedra, Gnetum, and Welwitschia constitute the gymnosperm order Gnetales of still unclear phylogenetic relationships within seed plants. Here we review progress over the past 10 years in our understanding of their species diversity, morphology, reproductive biology, chromosome numbers, and genome sizes, highlighting the unevenness in the sampling of species even for traits that can be studied in preserved material, such as pollen morphology. We include distribution maps and original illustrations of key featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 145 publications
(234 reference statements)
0
72
0
Order By: Relevance
“…Prior studies using fast-evolving chloroplast genes (Magall on & Sanderson, 2002;Rydin et al, 2002) showed the same relationships that we recovered with more slowly evolving genes that were more easily aligned for the group (i.e., atpB, rbcL, and matK). In contrast, other previous studies using single or multiple genes from the chloroplast, mitochondrial, and nuclear genomes have supported Gnetales as sister to Pinaceae (Goremykin et al, 1996;Winter et al, 1999;Bowe et al, 2000;Chaw et al, 2000;Frohlich & Parker, 2000;Gugerli et al, 2001;Burleigh & Mathews, 2004;Qiu et al, 2007) or to conifers Burleigh & Mathews, 2004;Ran et al, 2010; also see review by Ickert-Bond & Renner, 2016). Recently, protein-coding sequence data from the plastid genome for 78 genes from 360 green plant taxa recovered Gnetales as sister to non-Pinaceae conifers, placing Gnetales as sister to a clade of Araucariales þ Cupressales, and the Gne-Arau-Cup clade is then sister to Pinales (Ruhfel et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Prior studies using fast-evolving chloroplast genes (Magall on & Sanderson, 2002;Rydin et al, 2002) showed the same relationships that we recovered with more slowly evolving genes that were more easily aligned for the group (i.e., atpB, rbcL, and matK). In contrast, other previous studies using single or multiple genes from the chloroplast, mitochondrial, and nuclear genomes have supported Gnetales as sister to Pinaceae (Goremykin et al, 1996;Winter et al, 1999;Bowe et al, 2000;Chaw et al, 2000;Frohlich & Parker, 2000;Gugerli et al, 2001;Burleigh & Mathews, 2004;Qiu et al, 2007) or to conifers Burleigh & Mathews, 2004;Ran et al, 2010; also see review by Ickert-Bond & Renner, 2016). Recently, protein-coding sequence data from the plastid genome for 78 genes from 360 green plant taxa recovered Gnetales as sister to non-Pinaceae conifers, placing Gnetales as sister to a clade of Araucariales þ Cupressales, and the Gne-Arau-Cup clade is then sister to Pinales (Ruhfel et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Extant species of Gnetum are unusual among gymnosperms in being restricted to warm, mesic habitats 41 ; this contrasts to conifers that are adapted to cold and water-stressed environments. An analysis of genes involved in water and cold stress revealed some substantial differences between conifers and Gnetum.…”
Section: Water Stressmentioning
confidence: 99%
“…Ephedra L. (Gnetales) is another arid‐adapted genus and contains about 56 species distributed evenly between the deserts of the Old and New World (Stapf, ; Ickert‐Bond, ; Ickert‐Bond & Renner, ). Phylogenetic relationships based on nrDNA and cpDNA show six Mediterranean species form a grade at the base of the phylogeny, while the remaining 50 species from a well‐supported clade.…”
Section: Relicts Of Madrean‐tethyan Elementsmentioning
confidence: 99%